Experimental investigation of decomposition of signal energy for damage detection of jacket type offshore platforms. (2nd September 2022) - Rahman Shokrgozar, Hamed; Asgarian, Behrouz; Aghaeidoost, Vahid
ABSTRACT: Steel jacket-type offshore platforms are operating in extreme environmental conditions and are prone to various damages. Thus, using structural health monitoring techniques prevents irreparable damages, long-term out of services, and losses. Several methods, such as physical and data-driven models-based, are presented for damage detection. In this paper, the experimental response of a prototype model with various damage scenarios has been measured. The prototype was excited using an eccentric-mass actuator, and dynamic responses were applied to identify damage locations using the decomposition of the signal energy approach. This approach could overcome the weaknesses of other energy methods. These methods don't demonstrate the location and intensity of damages when a wide range of damages exists in the structure. However, the DSE approach can predict all damages in a prototype with reasonable accuracy. Therefore, the DSE method can be proposed as an acceptable method for structural health monitoring for steel jacket-type offshore platforms.